2015
DOI: 10.1111/biom.12419
|View full text |Cite
|
Sign up to set email alerts
|

Using the Whole Cohort in the Analysis of Countermatched Samples

Abstract: We present a technique for using calibrated weights to incorporate whole-cohort information in the analysis of a countermatched sample. Following Samuelsen's approach for matched case-control sampling, we derive expressions for the marginal sampling probabilities, so that the data can be treated as an unequally-sampled case-cohort design. Pseudolikelihood estimating equations are used to find the estimates. The sampling weights can be calibrated, allowing all whole-cohort variables to be used in estimation; in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…The results for continuous variables showed that pseudolikelihood with calibrated weights under countermatching performs better than the other methods and it is also useful to detect interaction. Similar results for time‐fixed variables have been found before . However, in the time‐fixed setting, partial likelihood sometimes worked better than pseudolikelihood.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The results for continuous variables showed that pseudolikelihood with calibrated weights under countermatching performs better than the other methods and it is also useful to detect interaction. Similar results for time‐fixed variables have been found before . However, in the time‐fixed setting, partial likelihood sometimes worked better than pseudolikelihood.…”
Section: Discussionsupporting
confidence: 86%
“…They were first introduced by Samuelsen for simple matching. Rivera et al , showed that, for countermatching designs, the probabilities are πk=1bkXiXk(1pk(Xi)), where b i is the time at which the subject enters the study, pk(t)=P(ktruescriptR~(t))={mAk(t)nAk(t)ifAk(t)At(t)mAk(t)1nAk(t)1ifAk(t)=At(t) is the inclusion probability for k at time t , A k ( t ) denotes the stratum to which subject k belongs at time t , and n l ( t ) is the stratum size at time t .…”
Section: Model and Parameter Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the recent literature in the independent data setting has sought to use survey sampling techniques, such as calibration, to improve statistical efficiency of standard IPW estimators . Central to the appeal of these techniques is that they facilitate the use of information that is readily available on all participants in the initial cohort but was not used in the design . A second key development of this paper, therefore, is a general framework for the use of calibration as a means to increasing efficiency in the cluster‐correlated data setting, together with practical guidance on how to operationalize the framework in practice.…”
Section: Introductionmentioning
confidence: 99%